An analysis of variations in body movement difficulty of 2016 Olympic Games rhythmic gymnast candidates - Agopyan, A.; Serdil Örs, B. (International Journal of Performance Analysis in Sport, 2019)
The aim of this study was to determine the use and the variety of body movement difficulty in the routines of individual rhythmic gymnasts aiming to compete in the 2016-Olympic Games, both those who qualified and those who did not. The research data was collected from the routines of 24 rhythmic gymnasts, from a total of 96 videos that were recorded during an Olympic qualification competition for the 34th Rhythmic Gymnastics World Championships of 2015 in Stuttgart/Germany. The gymnasts were divided into G11-15, the top 15 gymnasts, and G216-24, the remaining 9 gymnasts. The number of body movements (jumps/leaps, balances and rotations) and their comparative execution "difficulty" values were examined by quality and quantity. Penché rotation on a flat foot (79.2%), a jeté with a turn jump (66.67%) and balancing with a high back scale leg (57.29%) were the most frequently used body movements. The preferences of G1 gymnasts over G2 gymnasts for different types of static and dynamic difficulties across different movements even where there was not a wide variety. Rhythmic gymnasts at different performance levels generally tend to use the same body movement difficulties for all of their routines and this clearly indicates a lack of body difficulty variation.